Corporate Social Responsibility and Sustainable Development of Tourist Destinations - An Analysis from the Perspective of the Developing Regions in the European Context - Gabriela Carmen Pascariu; Ramona Frunz\~a (CES Working Papers, 2012)
Tourism is one of the most important industries in the European Union economy, with a great contribution to the general dynamic of the integration process and to the fulfillment of the Union strategic objectives. As a result, the last two decades have increasingly associated more to urism with the European policies, in a doctrinaire context defined by the option for sustainable development which correlates sustainable regions, sustainable tourists and sustainable enterprises in an integrated concept in the field of tourism. This paper deeply analyses the way in which the tourism enterprise can be associated with the sustainable development pattern, by valorizing the corporate social responsibility (CSR) principles. The analysis is qualitative, on the specific of the developing tourist destinations. The work is divided into three parts: explanation of the European context, insisting on the main tourism – regional development correlations, from the point of view of the sustainable development pattern; argumentation of the tourism enterprises necessity to take on economic, social and environment responsible practices in the sustainable development of the tourist destinations; the analysis of the advantages of being placed on the alternative markets from the perspective of ensuring the complementarity of the tourist actors and the receiving areas interests in an integrated system of sustainable and responsible management of the tourist region. The analysis leads to the better understanding of the potential contribution which the sustainable practices from the tourist industry can have to the sustainable growth of the developing regions.
Keywords: M14; R11; L83; 330; corporate social responsibility; sustainable regional development; European tourism Romania